Automated impedance manometry analysis as a method to assess esophageal function. Issue 5 (22nd January 2014) - Rommel, N.; Van, L.; Tack, J.; Omari, T. I.
Abstract Background Diagnostic evaluation of non‐achalasia esophageal dysphagia remains challenging because of a lack of a clear relationship between symptoms, esophageal contraction patterns, and esophageal bolus flow. This study evaluates a novel approach to pressure‐impedance analysis called automated impedance manometry (AIM) analysis in relation to bolus characteristics, Chicago classification metrics, bolus perception, and dysphagia. Methods AIM analysis was performed on esophageal high resolution manometry‐impedance recordings from 12 healthy controls and 15 patients with dysphagia. In each subject, 10 liquid, 10 semisolid, and 10 solid swallows were analyzed using AIMplot software. Key Results This study demonstrated that (i) esophageal pressure‐flow parameters differ with bolus type (liquid, semisolid, and solids), (ii) impedance at peak pressure parameter can discriminate normal from dysphagic subjects with high accuracy on a cut‐off threshold at 2400 Ohms (kappa 0.77, sensitivity 0.83, and specificity 0.93), and (iii) nadir impedance and impedance at peak pressure highly correlate with perception of esophageal bolus flow (r = −0.65, p = 0.02; r = −0.70, p = 0.01 resp). Conclusions & Inferences This study presents novel esophageal pressure‐flow variables in control subjects and in a cohort of patients with dysphagia. These variables are altered in relation to bolus consistency and can discriminate between subjects with and without symptoms of dysphagia. For the first time, we present high resolution esophageal pressure‐flow variables that accurately link in with patient perception of esophageal bolus hold up.